Evaluation of uric acid levels and other biochemical parameters among Gout patients with Ketogenic diet in Erbil province: Biochemical parameters among Gout patients with Ketogenic diet - Muhammad, Kwestan R. (Cellular and Molecular Biology, 2024)
Gout is a systemic disorder that occurs due to an accumulation of uric acid crystals in the tissues. The association between the Ketogenic diet and uric acid concentration has been poorly established. This study aims to evaluate and assess the association of Serum uric acid and other variables with ketogenic diet among Gout patients in comparison with Healthy control subjects. A case-control observational study. Subjects were grouped into Group I (Gout patients-103 individuals) and Group II (healthy Subjects-55 individuals). Parameters of Serum creatinine, blood urea, and uric acid were assessed for both groups. The study population included 51.3% of male and 48.7% of female participants, with an age range of 20-74, with a mean of 35.72±13.69 years old. Ketogenic and meat-rich diet as strong risk factors for Gout were higher among all case groups (45.6%) and (92.2%), respectively. The Pearson’s correlation coefficient of serum uric acid with other variables showed that the relation between serum uric acid with age, and weight among gout patients was found to be a weakly positive correlation and statistically significant (r=0.24, P= 0.013), and (r=0.22, P=0.026) respectively. This prospective study confirms that a ketogenic diet and a diet rich in meat have been associated with an increased incidence of gout. Indeed, results have shown that the ketogenic diet might have an increasing effect on serum uric acid. The frequencies of comorbidities have been constantly shown to be increased in gout.